PROGRAM FOR GAIN IN HEALTH OF THE DRAFT AGE PERSONNEL (BASED ON THE REPORT PRESENTED IN THE PANEL SESSION OF THE PRESIDIUM OF THE RUSSIAN ACADEMY OF MEDICAL SCIENCES, NOVEMBER 29, 2006) - A.A. Baranov; V.R. Kuchma (Вопросы современной педиатрии, 2007)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2007;6(2):8-12)